PERSEPSI SISWA TENTANG KOMPETENSI GURU AKUNTANSI SMK NEGERI 1 SURAKARTA TAHUN 2016 - Ramadhani, Cahya Hati; ., Siswandari; Octoria, Dini (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThe objectives of this research are to (1) investigate studentsâ perception towards Accounting teachersâ competencies at SMK Negeri 1 Surakarta; and (2) test the differences of studentsâ perception towards pedagogy competency and professional competency of Accounting teachers at SMK Negeri 1 Surakarta. This research used the descriptive research method. It was conducted at SMK Negeri 1 Sura-karta from February until October 2016. Its population was all of the Accounting students in SMK Negeri 1 Surakarta. The samples of research were determined through purposive sampling technique. The sam-ples were the Accounting students of class XII with total samples 74 students. The data were collected through questionnaire. The questionnaire were used to measure studentsâ perception towards pedagogy competency and professional competency of Accounting teachers. The data were analyzed by using the descriptive quantitative method, then followed by one sample t test with significance rate at 0,05. The re-sults of research are as follows: (1) studentsâ perception towards pedagogy competency of Accounting teachers is good. This is showed by the understandings of the students with score amount 224,63, the im-plementation of educated and dialogic teaching and learning process with score amount 240,8, the use of learning technologies with score amount 212,5, and the implementation of learning results evaluation with score amount 233,33. (2) Studentsâ perception towards professional competency of Accounting teachers are good with score amount 235,67. (3) Studentsâ perception towards pedagogy competency and profes-sional competency of Accounting teachers are good with score amount 231,74. (4) There are differences between studentsâ perception towards pedagogy competency and professional competency of Accounting teachers (tstat 81,166 >tcrit 1,9930).Keywords: Studentsâ perception, accounting teachers, teachersâ competencies, SMKABSTRAKPenelitian ini bertujuan untuk (1) mengetahui persepsi siswa terhadap kompetensi guru Akuntansi di SMK Negeri 1 Surakarta; dan (2) menguji perbedaan persepsi siswa terhadap kompetensi pedagogik dan kompetensi professional guru Akuntansi SMK Negeri 1 Surakarta. Penelitian ini menggunakan metode deskriptif kuantitatif. Penelitian dilaksanakan di SMK Negeri 1 Surakarta dari bulan Februari hingga Ok-tober 2016. Populasi dalam penelitian ini terdiri dari seluruh siswa jurusan Akuntansi di SMK Negeri 1 Surakarta. Teknik pengambilan sampel yang digunakan adalah teknik purposive sampling. Sampel yang terpilih adalah siswa kelas XII Akuntansi dengan jumlah 74 siswa. Teknik pengumpulan data menggunakan angket. Angket digunakan untuk mengukur persepsi siswa terhadap kompetensi pedagogik dan kompetensi profesional guru Akuntansi. Analisis data yang digunakan adalah dengan analisis statistik deskriptif dan dilanjutkan dengan uji t untuk satu sampel dengan taraf signifikansi 0,05. Hasil penelitian adalah sebagai berikut: (1) persepsi siswa terhadap kompetensi pedagogik guru Akuntansi adalah baik. Hal ini ditunjukkan dengan pemahaman terhadap peserta didik dengan skor sebesar 224,63, pelaksanaan pembelajaran yang mendidik dan dialogis dengan skor sebesar 240,8, pemanfaatan teknologi pembelajaran dengan skor sebesar 212,5, dan pelaksanaan evaluasi hasil belajar dengan skor sebesar 233,33. (2) Persepsi siswa terhadap kompetensi profesional guru Akuntansi adalah baik dengan skor sebesar 235,67. (3) Persepsi siswa tentang kompetensi pedagogik dan kompetensi professional guru Akuntansi adalah baik dengan skor sebesar 231,74. (4) Terdapat perbedaan persepsi siswa terhadap kompetensi pedagogik dan kompetensi profesional guru Akuntansi (thitung 81,166 > ttabel 1,9930).Kata Kunci: Persepsi siswa, guru Akuntansi, kompetensi guru, SMK